2011
DOI: 10.1080/00224540903368541
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and Interpersonal Relationships: A Nepalese Investigation

Abstract: The present study examined the practice of forgiveness in Nepal. A model relating collectivism and forgiveness was examined. Participants (N = 221) completed measures of collectivism, individualism, forgiveness, conciliatory behavior, and motivations for avoidance and revenge toward the offender. Collectivism was positively related to forgiveness. Forgiveness was strongly related to conciliatory behavior and motivations for avoidance and revenge toward the offender. Decisional forgiveness was a stronger predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 18 publications
2
37
0
1
Order By: Relevance
“…Fourth, we used a measure of conciliatory behavior (CB) toward an offender (Watkins et al, 2011). This measure consists of six items that measure the degree to which participants have engaged in behaviors that indicate attempts at reconciliation with the offender (e.g., “I took steps toward reconciliation: wrote him or her, called him or her, expressed love, showed concern, etc.”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, we used a measure of conciliatory behavior (CB) toward an offender (Watkins et al, 2011). This measure consists of six items that measure the degree to which participants have engaged in behaviors that indicate attempts at reconciliation with the offender (e.g., “I took steps toward reconciliation: wrote him or her, called him or her, expressed love, showed concern, etc.”).…”
Section: Methodsmentioning
confidence: 99%
“…Participants indicate their agreement with each item on a 5-point rating scale, from 1 = strongly disagree to 5 = strongly agree . This measure had a Cronbach’s alpha coefficient of .62 (Watkins et al, 2011). Scores on this measure also showed evidence of construct validity and were related to forgiveness.…”
Section: Methodsmentioning
confidence: 99%
“…Watkins et al (2011) found that collectivism was associated with decisional rather than emotional forgiveness, conciliatory behaviors, and avoidance of revenge motivations. Watkins et al (2011) found that collectivism was associated with decisional rather than emotional forgiveness, conciliatory behaviors, and avoidance of revenge motivations.…”
Section: Interpersonal Forgivenessmentioning
confidence: 95%
“…Of particular relevance to the present research are studies that demonstrate that when collective identity is salient among victims, they exhibit greater prosocial responses to mistreatment, and lower antisocial responses (e.g., Bobocel, 2013;Bobocel & Zdaniuk, 2010;Fu, Watkins, & Hui, 2004;Hook, Worthington, Utsey, Davis, & Burnette, 2012a, Hook et al, 2012bHui & Bond, 2009;Karremans, Van Lange, & Holland, 2005;Neto & Mullet, 2004;Watkins et al, 2011). For example, Bobocel and Zdaniuk (2010) found that the stronger victim's collective identity, whether situationally primed or measured, the more prosocial their responses toward an offender (e.g., forgiveness, greater helping).…”
Section: Background Theory and Hypothesesmentioning
confidence: 97%